(untitled) (International Journal of Innovative Technologies in Economy, 2021)
The article substantiates the role of artificial intelligence in procuring the management of innovation and structural transformation of the economy. The analysis of structural shifts in gross value added in the economy of Ukraine during 2002–2019 is carried out. Solow’s residuals are calculated for the primary, secondary and tertiary sectors. The expediency of managing the innovative and structural transformation of Ukraine’s economy on the basis of changes in the level of Solow’s residual in that sector and in the period of time determined by big data analysis by artificial intelligence is proved. A VAR model was built in the EViews environment for Solow’s residuals in three sectors of the Ukrainian economy. Based on variance decomposition and IRF, it is established that increasing the share of intermediate consumption by the secondary sector of education, ICT, professional, scientific and technical services will increase Solow’s residual in the secondary sector in two years, in the tertiary sector in three years and in the primary sector in four years, which will affect the increase in output in Ukraine during these three years.